Work values of nurses in the nursing department and perceived satisfaction of in-patient and out-patient clients at Medical Mission Group Hospital, Calapan City - Reyes, Claro M.
This study was an assessment of the work values of the nurses in relation to perceived patients? satisfaction at Medical Mission Group Hospital, Calapan City, Oriental Mindoro, a 30-bed tertiary hospital with more than 70 regular nurses, including trainees and probationary. The objectives of the study are to consider the factors/variables that influence the nurses work values, to determine the patient?s perceived satisfaction in the work values shared by the staff nurses of MMG Hospital, to relate the work values that has an important bearing in the satisfaction of patients at MMG Hospital, to compare the differences in the perceived responses of in-patient and out-patient satisfaction and to provide an initial data on benchmarking patient?s satisfaction. This is a descriptive correlational study conducted at the MMG Hospital from January to April 2011, using survey questionnaires distributed randomly selected staff nurses, admitted patients and out patients during this period. The work values were limited only to three identified work values adapted to our culture as respect for person, beneficence and veracity. Result showed that work value in terms of respect for person exhibited by nurses was perceived to be ?always? by the respondents. This means that the nurses of MMG has shown their appreciable performance on ethical principles which are practiced as a professional duty and recognition of patient rights. Work values in terms of beneficence as practiced by the nurses received a high descriptive rating of ?always.? All indicators of beneficence are always done and are indicative of the nurses? competence in reference to their values in their work environment. In terms of veracity, all indicators also received the high descriptive rating of ?always.? This means that the principle of veracity binds the MMG staff nurses and the patient to tell the truth. Relationship in work values between veracity and inpatients satisfaction was found to be significant. Relationship in work values between beneficence and outpatient?s satisfaction was found to be significant. In-patients satisfaction at MMG Hospital in terms of work values extended by staff nurses obtained a descriptive rating of ?very much satisfied.? However, outpatient client were ?much satisfied? only on the work values given by nurses in all indicators. Comparing the inpatient and outpatient satisfaction, the outpatients were less satisfied. However, when t test for difference was computed, the difference was not significant.
Management study (MHA)--University of the Philippines Manila, 2011
Keywords: Patient Satisfaction